Empirical welfare analysis with preference heterogeneity - Peter Haan; Andre Decoster (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We apply recently proposed individual welfare measures in the context of preference heterogeneity, derived from structural labour supply models. Contrary to the standard practice of using reference preferences and wages, these measures preserve preference heterogeneity in the normative step of the analysis. They also make the ethical priors, implicit in any interpersonal comparison, more explicit. Information on preference heterogeneity is obtained from a structural discrete choice labor supply model for married women estimated on microdata from the Socio Economic Panel (SOEP) in Germany. We construct welfare orderings of households according to the different metrics, each embodying different ethical choices concerning the treatment of preference heterogeneity in the consumption-leisure space and provide empirical evidence about the sensitivity of the welfare orderings to different normative principles. We also discuss how sensitive the assessment of a tax reform is to the choice of different metrics.
Keywords: C35; D63; H24; 330